Kajian Kuat Tekan Material Tanah Lempung dan Pasir Berbahan Campur Sampah Plastik Rumah Tangga - Taufiq Ilham Maulana (Semesta Teknika, 2016)
In Indonesia, the waste has become a national issue which must be managed in a comprehensive and integrated from upstream to downstream in order to provide economic benefits, healthy for the community, and safe for the environment, and can change people's behavior. From various types of waste, plastic is a very dangerous household waste. One effort to reduce dam use plastic waste is to be made as mixing clay and sand to produce material that can be used as building materials. In this research molten plastic waste was mixed with clay and sand with variations of ratio plastic-sand and plastic-clay is 1: 2, 1: 3 and 1: 4. The results revealed that the optimum ratio of plastic-sand mixture is 1: 3 with a compressive strength of 13.5 MPa and the optimum mix of plastic-clay is 1: 2 with a compressive strength of 14.21 MPa. The collapse pattern that occurred in the plastic-sand mixture was shear failure that caused test object splitting, while the plastic-clay mixture is shear failure, but without causing the test object splitting.